AV3V-LESION IMPAIRS RESPONSES INDUCED BY CHOLINERGIC ACTIVATION OF SFO IN RATS - Colombari, DSD; Saad, W. A.; Camargo, LAD; Renzi, Antonio [UNESP]; Deluca, L. A.; Colombari, Eduardo [UNESP]; Menani, José Vanderlei [UNESP] (Amer Physiological Soc, 1992)
This study was performed to investigate the effect of lesion of the anteroventral third ventricle (AV3V) region on the pressor, bradycardic, dipsogenic, natriuretic, kaliuretic, and antidiuretic responses induced by cholinergic activation of the subfornical organ (SFO) in rats. Male Holtzman rats with sham or electrolytic AV3V lesion were implanted with a stainless steel cannula directly into the SFO. Microinjection of the cholinergic agonist carbachol (2 nmol) into the SFO of sham rats induced natriuresis (563 +/- 70 mueq/120 min), kaliuresis (205 +/- 13 mueq/120 min), antidiuresis (10.4 +/- 0.5 ml/120 min), water intake (9.3 +/-1.4 ml/h), bradycardia (-42 +/- 11 beats/min), and increased mean arterial pressure (53 +/- 3 mmHg). In AV3V-lesioned rats (1-5 and 14-18 days), there was a reduction of natriuresis (23 +/-11 and 105 +/- 26 mueq/120 min, respectively), kaliuresis (92 +/- 16 and 100 +/- 17 mueq/120 min), water intake (2.5 +/- 0.9 and 1.8 +/- 1.0 ml/h), and arterial pressure increase (17 +/- 2 and 16 +/- 2 mmHg) induced by carbachol into the SFO. Increased antidiuresis (6.0 +/- 1.0 and 5.2 +/- 0.7 ml/120 min, respectively) and tachycardia (39 +/- 4 and 15 +/- 12 beats/min) instead of bradycardia were also observed in both groups of AV3V-lesioned rats. These results show that cholinergic activation of the rat SFO produces marked natriuresis and kaliuresis in addition to the well-known pressor and dipsogenic responses. They also show that the AV3V region plays an important role in the cardiovascular, fluid, and electrolytic changes induced by cholinergic activation of the SFO in rats.
Keywords: NATRIURESIS; KALIURESIS; ARTERIAL PRESSURE; WATER INTAKE; ANTEROVENTRAL 3RD-VENTRICLE REGION; DIURESIS; SUBFORNICAL ORGAN